2002
DOI: 10.1111/j.1553-2712.2002.tb00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Pulmonary Score: An Asthma Severity Score for Children

Abstract: These data support the construct and criterion validities of the PS as a measure of asthma severity among children in the ED. The PS is a practical substitute to estimate airway obstruction in children who are too young or too sick to obtain PEFRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 7 publications
0
40
0
2
Order By: Relevance
“…The few clinical scores cited that have been subject to more rigorous study, including measures of reliability, validity, and responsiveness, include the Preschool Respiratory Assessment Measure (PRAM), 6 the Clinical Asthma Score (CAS), 11 the Asthma Severity Scale (ASS), 12 the Pulmonary Index (PI), 5 and the Pulmonary Score (PS). 13 Characteristics of these scores and their validation are summarized in Table 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few clinical scores cited that have been subject to more rigorous study, including measures of reliability, validity, and responsiveness, include the Preschool Respiratory Assessment Measure (PRAM), 6 the Clinical Asthma Score (CAS), 11 the Asthma Severity Scale (ASS), 12 the Pulmonary Index (PI), 5 and the Pulmonary Score (PS). 13 Characteristics of these scores and their validation are summarized in Table 7.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation coefficients in our study were somewhat lower than those reported for the PS, which ranged from 0.44 to 0.67. 13 However, although PEFR is a good indicator of the degree of airway obstruction, it is not a criterion standard. 16 Interpreting the relationship between imperfect measures is problematic, but the magnitude of the correlation between the PASS and PEFR is similar to that reported for several other scores in the literature, as noted above.…”
Section: Limitationsmentioning
confidence: 99%
“…The PS is used routinely and has 3 domains (respiratory rate, wheeze, and degree of retractions) with 3 possible points per domain (score range 0 to 9). 28 …”
Section: Methodsmentioning
confidence: 99%
“…Although more than 16 severity scoring systems exist, many are difficult to use. 3 For example, some severity measures require blood gas analyses; others require numerous objective measures, or demanding assessments such as inspiratory/expiratory ratios. [4][5][6][7] The pulmonary score (PS) was developed to provide a ''userfriendly'' measure of asthma severity for children with an acute asthma exacerbation.…”
Section: Introductionmentioning
confidence: 99%